Legal Aspects Regarding the Validity of Electronic Signatures (DIGITAL SIGNATURE) as Evidence of Electronic - Sigit Ardiansyah; Abdul Hakim; Maya Jannah; Risdalina Siregar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this research is as a tool for developing a law that is accompanied by technological advances and causes the switch from the use of conventional signatures to electronic signatures ( Digital Signature ) and can find out how the position or validity of an electronic signature as evidence of electronic transactions before the law. By using normative juridical research methods, or research based on a legal norm, it can be concluded that the legal power of proving electronic documents signed with electronic signatures and used by legal subjects in making an agreement, it can be stated that electronic signatures can be used as proof of transactions electronically and obtain a legal position before the law, as stated in article 5 paragraph 1 of Law Number 11 of 2008 As amended by Law Number 19 of 2016 concerning Electronic Information and Transactions, it is explained that an Electronic Information or Document and its printout is legal evidence before the law. As long as the signature has 3 conditions, namely the existence of identity, integrity and no denial